Improving public enterprise performance : concepts and techniques - Powell, Victor (Geneva : International Labour Office, 1987)
This publication suggests action programmes to improve the performance of public enterprises. It is written primarily for those who have responsibility for public enterprise systems in developing countries who would like to initiate action to improve the performance of the enterprises in these systems
"Prepared within the INTERMAN project with the financial support of the UNDP Inter-regional Programme."
Includes bibliographies.
osc 01/02/2019
Loans
Keywords: Government business enterprises; Government executives